ELA-11 protects the heart against oxidative stress injury induced apoptosis through ERK/MAPK and PI3K/AKT signaling pathways - Wang, Xuejun; Zhang, Li; Feng, Mengwen; Xu, Zhongqing; Cheng, Zijie; Qian, Lingmei (Frontiers in Pharmacology, 2022)
Increasing evidence revealed that apoptosis and oxidative stress injury associated with the pathophysiology of DOX-induced myocardial injury. ELABELA(ELA) is a newly identified peptide with 32 amino acids, could normalized hypertension with exogenous infusion. However, the effect of 11-residue furn-cleaved fragment (ELA-11) is still unclear. We first administrated ELA-11 in DOX-injured mice and measured the cardiac function and investigated the effect of ELA-11 in vivo. We found that ELA-11 alleviated heart injury induced by DOX and inhibited cardiac tissues from apoptosis. In vitro, ELA-11 regulated the sensitivity towards apoptosis induced by oxidative stress with DOX treatment through PI3K/AKT and ERK/MAPK signaling pathway. Similarly, ELA-11 inhibited oxidative stress-induced apoptosis in CoCl2-injured cardiomyocytes. Moreover, ELA-11 protected cardiomyocyte by interacting with APJ by using ML221. Hence, our results revealed a protective role of ELA-11 in oxidative stress-induced apoptosis in DOX-induced myocardial injury.